Pembelajaran Inquiry Based Learning (IBL) untuk Meningkatkan Kreatifitas dan Prestasi Belajar Thermokimia Siswa Kelas XI IPA1 di SMA Negeri 5 Metro - R. Tri Endah W. (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
Inquiry Based Learning (IBL) is a Science process skill approach, where students are directed to master inquiry based skills. This IBL-based classroom action research turned out to be able to improve the creativity and learning achievement of students in class XI IPA1. Learning Outcomes 1) Average Pre-Cycle learning achievement: 64.9; increased in Cycle I: 69.1 and in Cycle II: 83.8. Thus there is an increase in the average chemistry learning achievement from Pre-Cycle, Cycle I, and Cycle II. The increase has reached the planned indicator, which is 7.5; 2) In Cycle II there was no predicate of Dislikes and Dislikes, 78% of students were predicated on Suka, and 22% of students were predicated on Sangat Suka. The predicate Suka and Tidak Suka decreases and shifts the predicate Suka and Sangat Suka. Suka and Sangat Suka Predicates amounted to 94% exceeding the planned achievement indicators, the cycle was stopped.